Collaborative Consumption, Social Capital and the Neighbourhood. An Approximation - Schnur, Olaf; Günter, Henning (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
Both, neighbourhoods and Collaborative Consumption (sometimes also referred to as Sharing Economy or New Economy), are the loci of interest in current scientific and political discussions that oscillate between the global and the local. This article aims to link the concepts’ potential procedural similarities more closely than has been done so far. Both of these concepts consider societal problems and potentials to be affecting the micro level; they form a part of the currently undergoing local shift. In order to explore this potential in more detail, we will present a typology of different platforms of Collaborative Consumption that takes into consideration both, social capital and relevant characteristics of a neighbourhood. Based on this analysis, we will argue that many of these platforms, despite their emphasis on neighbourly relationships, don’t necessarily foster an accumulation of social capital within neighbourhoods. However, there is one distinguished type, we define it as “the autotelic-oriented one”, which can potentially have a positive impact on neighbourhood development. Only this type enables the accumulation of social capital, attempts to overcome socio-economic barriers and provides reciprocity mechanisms for the exchange of favours. This type could be fruitful for neighbourhoods and should be taken into account more seriously by researchers and professionals in this field. We will argue that Collaborative Consumption can hence result in a “neighbourhood 2.0” – a community that is complementarily strengthened through web-based services.